Correlation between radiologic and pathologic extranodal extension in HPV‐associated oropharyngeal cancer: Systematic review. Issue 12 (7th September 2022) - Morey, Tristan; Hodge, John‐Charles; Stern, Cindy; Krishnan, Suren; Foreman, Andrew
Abstract: Pretreatment determination of extranodal extension (ENE) has significant clinical implications in human papillomavirus positive (HPV+) oropharyngeal squamous cell carcinoma (OPSCC). Unfortunately there is no gold‐standard imaging modality for radiological assessment of ENE in HPV+ OPSCC, leading to subjective assessments and complex decision making concerning ENE. A systematic review of diagnostic test accuracy was therefore undertaken, with five databases systemically searched to evaluate the diagnostic performance of an imaging modality for detection of ENE in HPV+ OPSCC. A meta‐analysis was conducted on four CT studies using a random‐effects model. While a narrative synthesis was provided for the studies using PET/CT and "CT and MRI." Out of 1772 hits, six studies were included in the review. Meta‐analysis on four CT studies showed CT had an overall sensitivity of 77% and specificity of 60%. PET/CT had a sensitivity of 37.5% and specificity of 97%. "CT and MRI" had a sensitivity of 62% and specificity of 78%. Further diagnostic studies involving CT, PET/CT and MRI are ultimately required.